(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Maternal morbidity and mortality remain major public health challenges in low-resource settings, with obstetric hemorrhage and severe anemia being the leading contributors. Timely blood transfusion plays a critical role in reducing complications and improving outcomes in obstetric emergencies, particularly among referred patients. Objective: To determine the need and indications for blood transfusion among obstetric referrals to a tertiary care hospital in Karachi. Methods: This observational cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, Jinnah Postgraduate Medical Centre (JPMC), Karachi, over Six-months period in the duration from 1st November, 2022 to 30th April, 2023. A total of 280 pregnant women aged ≥18 years referred from primary, secondary, or tertiary healthcare facilities were included through convenience sampling. Data were collected using a structured proforma, capturing demographic details, referral status, obstetric history, and blood transfusion requirements. Data analysis was performed using R software, with descriptive statistics reported as frequencies, percentages, means, and standard deviations. Results: Of the 280 obstetric referrals, 102 (36.4%) required blood transfusion. Postpartum hemorrhage was the leading indication for transfusion (n = 59, 57.8%), followed by severe anemia (n = 29, 28.4%) and antepartum hemorrhage (n = 14, 13.8%). The majority of transfused women (66.7%) received blood in the postpartum period. The mean number of blood units transfused was 2.1 ± 0.8 units. Secondary healthcare facilities accounted for the highest proportion of referrals (49.3%), and transfusion needs were significantly higher among referrals from secondary and private maternity facilities compared to primary care units. Conclusion: A substantial proportion of obstetric referrals required blood transfusion, primarily for postpartum hemorrhage and severe anemia. Strengthening antenatal anemia management, improving emergency obstetric care at peripheral centers, and implementing Patient Blood Management strategies are essential to optimize transfusion practices and improve maternal outcomes in low-resource settings.